Pemberdayaan Ekonomi Produktif Warga Binaan Lapas Kelas II A Labuhan Ruku Melalui Program Pelatihan Teknik Dasar Pengelasan - Battra Siahaan, Enzo Wiranta; Sitanggang, Hodmiantua; Sidabutar, Rotama Arifin (JPM: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to improve the technical skills and job readiness of inmates at Class IIA Labuhan Ruku Prison through basic welding training. The training method applied a combination of hands-on practice, lectures, and intensive mentoring, involving 20 participants, most of whom had no prior welding experience. The results indicated a significant improvement in participants’ technical skills, motivation, and self-confidence, with 90% of them successfully performing basic welding independently. Participants’ satisfaction with the program was also high, with an average score of 4.5 out of 5. The limitation of this program lies in its short duration and the absence of official certification as a formal recognition of participants’ skills. The absence of formal certification limits participants’ access to directly enter the industrial labor market, thus the outcomes of the training are more optimally directed toward strengthening economic independence through small welding workshops or ent